Strategi Pengendalian Hambatan Approach Surface Runway 27 untuk Kesiapan Cat II di Bandar Udara Ngurah Rai - Deny Nur Setiawan; I Wayan Dikse Pancane; I Nyoman gede Adrama; Agus Putu Abiyasa (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
The growth of aviation activities at I Gusti Ngurah Rai International Airport, Bali, has led to the rapid development of surrounding areas, potentially obstructing protected airspace. Obstacles on the approach surface of Runway 27 have become a critical concern, particularly for precision approach Category II (CAT II) operations, which require obstacle-free approach areas. This study aims to analyze obstacles within the approach area of Runway 27 and develop effective control strategies. Using a descriptive qualitative approach, data was collected through field observations, interviews, and documentation studies. The analysis follows the Obstacle Limitation Surfaces (OLS) standards according to ICAO and national regulations. The findings reveal obstacles such as mangrove vegetation, antennas, and ship activities in the Benoa Harbor area, which are located within the approach surface and could potentially impact the OLS limits. While these obstacles generally comply with existing regulations, their proximity to the threshold may reduce the safety margin of flight operations and limit CAT II implementation on Runway 27. This study proposes technical, operational, regulatory, and preventive strategies to improve obstacle control, enhancing aviation safety and ensuring the readiness for CAT II operations at the airport.